MENENTUKAN KOMPOSISI OPTIMAL DARI FAKTOR-FAKTOR YANG MEMENGARUHI KETAHANAN ASPAL DENGAN METODE TAGUCHI - YULIANDARI, GUSTI AYU PUTU; SRINADI, I GUSTI AYU MADE; SUMARJAYA, I WAYAN (E-Jurnal Matematika, 2013)
Taguchi method purpose to improve the quality of a product. This method can reduce the number of execution of the experiment when compared to using a full factorial method. measures taken, namely the calculation of degrees of freedom, the selection of orthogonal array to reduce the run, then calculating S/NR is used to determine the optimal composition of the factors that will affect the durability of asphalt. The results of this research that the optimal composition of the factors that affect the resistance of asphalt are aggregate of 6987.57 tons, temperature of 155? C, compaction speed 5 km/h, hardening time for 4 hours after paving before the opening of traffic at normal speed, thickness of 6.27 cm thick bitumen from the aggregate surface, body weight that is weighing 7 ton. Dimensions of factors is an area of ??5.598m.
Keywords: Taguchi Methods; Degrees of Freedom; Signal to Noise Ratio (S/NR); Orthogonal Array